Intensitas Peserta Didik Mengikuti TPA dalam Meningkatkan Kemampuan Membaca Al-Qur’an di MI Al-Hasanah - Irmayanti Safitri; Indry Nirma Yunizul Pesha; Khaidir Fadil (ARZUSIN, 2026)
Although the ability to read the Qur’an is a fundamental competence in Islamic education, studies that specifically examine the influence of the intensity of students’ participation in Taman Pendidikan Al-Qur’an (TPA) on improving Qur’anic reading ability at the madrasah ibtidaiyah level remain limited. This study aimed to analyze the intensity of students’ participation in TPA activities, the Qur’anic reading ability of Grade IV students, and the supporting and inhibiting factors for its improvement. The research employed a descriptive qualitative approach with a case study design involving 16 Grade IV students of MI Al-Hasanah selected through purposive sampling. Data were collected through interviews and documentation, then analyzed thematically. The findings showed that students with high-intensity participation in TPA experienced improvements in their Qur’anic reading ability, whereas students with low-intensity participation still encountered various difficulties in reading. Supporting factors for improving Qur’anic reading ability included learning interest and parental support, while inhibiting factors comprised digital game addiction and low learning motivation. These findings underscore the pivotal role of TPA in enhancing Qur’anic literacy among madrasah ibtidaiyah students and imply the need for synergy among madrasahs, TPA institutions, and parents to build a sustainable Qur’anic learning environment. The study also opens opportunities for further research using quantitative or mixed-methods approaches to examine the causal relationship between TPA participation intensity and Qur’anic literacy outcomes on a broader scale.